O desenvolvimento de inovações no setor de defesa no Brasil: um estudo do programa FX-2/Gripen NG - Brites, Ian Fabrício (2022)
This study is intended to address the themes of the Entrepreneurial State, Innovation and Defense through the FX-2/Gripen NG Program for Brazil. In order to demonstrate that the government can present itself far beyond a merely formal and bureaucratic entity, assuming the role of a strategic player in social and economic changes and evolutions, this research transits through multidisciplinary themes and draws from national and international sources in the areas involved. The initial approach goes through the issue of the entrepreneurial State and the redefinition of its role in society, seeking to present elements that collaborate with the understanding that not only do modern actions and mechanisms of state participation in the economy exist, but that such moments need to be demonstrated and absorbed by society in general, increasing the feeling of belonging and collectivity with what is public. In a second moment, innovation will be presented as one of the main tools through which these movements of modernization and progress of the State occurred, are taking place and could intensify over the years. The highlight in this topic is what is exposed in the OECD's Oslo Manual (2018) and the standardization of instruments that seek to measure innovations and generate reliable indices for comparison between different countries. Finally, a context on the national defense scenario will be pointed out as a prolific possible link between the entrepreneurial State and the innovation brought about, with the Gripen NG Program emerging as an object of analysis. In this scenario of international cooperation and transfer of high technology, Gripen NG demonstrates high potential to become an exponent in this context and to be one of the catalysts for future innovation actions for Brazil. In this way, the study aims to characterize the FX-2 Program (which gave rise to the Gripen NG Program), as well as to perceive, according to the orientation of the Oslo Manual (2018), the Innovations in Business Processes and Product Innovations presents in the FX-2 Program. The research elements used are essentially based on official written documental analysis on the matter, in addition to audiovisual elements produced in a web series by Saab about Gripen NG. In this way, it is possible to see how the innovation process has been taking place throughout the FX-2 Program, not only in direct technological and military terms, but also in industrial and knowledge production processes in the companies involved, as well as through the involvement of researchers and scientists in related fields. Likewise, it presents a latent field of research for the most varied sectors, in a theme with great aptitude for development and still not so well explored in the national academic scene, particularly in the civil sphere.